Produção de grãos, forragem, palhada e propriedades físicas em latossolo vermelho sob diferentes usos em sistemas de integração lavoura pecuária - Castagnara, Deise Dalazen (2012)
The study was conducted to evaluate the production and characteristics of oat straw in 2009 and the performance of corn in succession submitted to the different splitting of nitrogen. Also, the production of fodder and straw, structural and nutritional characteristics of oat and soil physical properties in the succession black oat / corn / oats / soybean / oats in the years 2009, 2010 and 2011. We adopted six land uses distributed in bands (P10 and P20: grazing height of the residue of 10 and 20 cm, C10 and C20: Cutting hay with height of the residue of 10 and 20 cm, SC w / SD - no grazing or cuts for tillage; SC w / PC - without grazing or cutting for conventional tillage) and three times in the design of randomized blocks. In the years 2009, 2010 and 2011 were performed respectively 3, 1 and 2 cuts or grazing oats. In 2009/2010 crop was sown corn crop and the harvest 2010/2011 soybean crop. Evaluations to determine production of straw were taken after grazing or cutting and drying prior to deployment to areas of summer crops. In maize were evaluated biometric characteristics, yield components and productivity. Sampling for determination of dry matter production, structural and nutritional characteristics of forage were taken at each cutting or grazing. The samples for the determination of physical characteristics of soil macroporosity, microporosity, total porosity and bulk density were made in layers 0 to 0.10 and 0.10-0.20 m at the end of each cycle of cultivation of oats or of summer crops. The completion of cutting or grazing reduces the deposition of straw by oats. Large quantities of straw oats reduce the productivity of corn. Different splitting of nitrogen do not affect the grain yield in oats. Better quality forage and better distributed throughout the autumn-winter period is achieved with the completion of cutting or grazing. In Oxisol, conventional tillage reduces density and increases microporosity and macroporosity and total porosity, while the cultivation of oats in the fall and winter harvest forage by cutting or grazing residual height of 10 cm or 20 does not alter the physical properties of soil